Preparation of Media for Growth and Isolation of Lactic Acid Bacteria by Using the Starch-Industry by- Products (Baghdad Science Journal, 2010)
By- products of corn starch industry were used to prepare media for propagation the lactic acid bacteria as a natural auxotroph. The by- products used were the corn steep water (S) and gluten extract (G) after a proper treatment to get them ready for media preparation. The results showed that it was possible to replace the peptone and meat extract by gluten extract in MRS medium. The growth was approximately similar to that obtained in standard MRS media. Corn steep water (S) was used as well and the growth enhanced by including Tween – 80 at 1% level. The later media named MZ, which was superior for growing standard and local strains and starters. The MZ medium modified by adding acetate and glacial acetic acid similarly to Rogosa media and was very efficient selection property for selecting and growing of lactobacilli only. There was no difference in the starter activities grown in MRS or MZ liquid media used to coagulate sterile whole milk and the developed acidity was at similar extent.